Feminicide In The Ottoman Empire: The Diyarbakır Example (1655-1866). - Akkoyun Özlü, Gülşen (Electronic Turkish Studies, 2026)
Femicide dates back to the earliest times of human history. This study attempts to identify the circumstances surrounding the murders of women in what is now Diyarbakır between 1655 and 1866. Due to the breadth of the scope of the study, it was limited to Diyarbakır, a city of socio-cultural significance throughout Ottoman history. It was determined that no study had directly addressed this issue in Diyarbakır during the 211-year period covered by this research. Therefore, the need to address such a topic arose, and an attempt was made to address this deficiency. The primary source of this research is the State Archives Presidency of the Republic of Turkey/Ottoman Archives. In addition, the 13-volume Diyarbekir Şer’iyye Sicilleri Amid Mahkemesi, prepared by Dicle University Faculty of Theology Publications based on the Ottoman Archives, and the 3-volume Divan-ı Hümâyûn Sicilleri Diyarbekir Ahkâm Registers, published by the same publishing house, were scanned. The case records found in the works were compared with the Ottoman Archives and used. The investigations revealed that 12 women were murdered in Diyarbakır. These women were from various professions, generally from the middle and lower classes of society. They were murdered by men of varying status, for various reasons, using various tools and methods, and, as is the case today, generally in homes. The subject was examined under the following headings: the locations/locations of the murders, the profiles of the victims and murderers, the means/method of murder, the dates of the events, and the court proceedings. Furthermore, a case record was discovered during this process in which a woman was tried for murder, and this record was included in the scope of the study.